Pemberdayaan Petani Hortikultura melalui Sosialisasi dan Pendampingan Budidaya Cabai Varietas Neno Tahan Virus di Desa Benai Kecil, Kabupaten Kuantan Singingi - Yunandra; Julita Saidi; Dian Rakhmad; Dedi Mulyadi; Alltop Amri Ya Habib; Rizki Oktavian; Elisa Apriliani; M. Joehari Jamili (JURPIKAT, 2026)
National chili demand continues to increase, but productivity at the farmer level remains low due to attacks by the whitefly (Bemisia tabaci Genn.) virus. Benai Kecil Village, Benai District, Kuantan Singingi Regency, Riau, is a horticultural center with low chili productivity (4–5 tons/ha), far below the potential of commonly used superior varieties. This community service activity aims to improve farmers' knowledge and skills in chili cultivation by initiating the use of the superior virus-resistant Neno variety. The program was implemented for five months with stages of socialization, field practice, mentoring, monitoring, evaluation, and follow-up. The results of the activity indicated that farmers improved their understanding and skills in chili cultivation techniques, including seeding, soil cultivation, maintenance, and pest and disease control. The evaluation showed that the Neno chili variety has the potential to be developed because it is adaptive to dynamic climate change and effectively reduces the risk of curly virus attacks. In addition, the use of virus-resistant varieties can also support environmentally friendly pest and disease control. This program demonstrates that the development of the superior Neno variety has the potential to be a sustainable strategy for increasing chili production while simultaneously strengthening food security and farmer welfare.